2002
DOI: 10.1007/s002850100112
|View full text |Cite
|
Sign up to set email alerts
|

Mode-doubling and tripling in reaction-diffusion patterns on growing domains: A piecewise linear model

Abstract: Reaction-diffusion equations are ubiquitous as models of biological pattern formation. In a recent paper we have shown that incorporation of domain growth in a reaction-diffusion model generates a sequence of quasi-steady patterns and can provide a mechanism for increased reliability of pattern selection. In this paper we analyse the model to examine the transitions between patterns in the sequence. Introducing a piecewise linear approximation we find closed form approximate solutions for steady-state patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 28 publications
2
97
1
1
Order By: Relevance
“…For reaction-diffusion systems on growing domains, which is a good model for the growth of organisms, we mention [3], [4], [34], [35]. Recently in [61] hair follicle arrangements in mice have been modelled by a reaction-diffusion system, where the WNT and DKK proteins serve as an activator and inhibitor, respectively, and experiments are combined with numerical computations.…”
Section: Previous Results On Peaked Solutionsmentioning
confidence: 99%
“…For reaction-diffusion systems on growing domains, which is a good model for the growth of organisms, we mention [3], [4], [34], [35]. Recently in [61] hair follicle arrangements in mice have been modelled by a reaction-diffusion system, where the WNT and DKK proteins serve as an activator and inhibitor, respectively, and experiments are combined with numerical computations.…”
Section: Previous Results On Peaked Solutionsmentioning
confidence: 99%
“…It is worth remarking here that all previous works except [17] and [20] have exclusively considered dilatation dynamics. Even in the different field of reaction-diffusion dynamics in which the dilution term was derived, the focus was on the limit in which it was irrelevant [18]. This work is devoted to exploring further the consequences of dilution, dilatation, and decorrelation and their effects on scaling of radial interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms for pattern transitions have been investigated in a class of reactiondiffusion systems by Crampin et al (2002), wherein a third possibility is also described in which splitting and insertion occur simultaneously. Schnakenberg (1979) proposed a hypothetical series of trimolecular autocatalytic reactions, for which the nondimensionalized concentrations of self-activating, v, and self-inhibiting, u, chemicals give the kinetic scheme…”
Section: Reaction Schemesmentioning
confidence: 99%
“…Transitions between patterns arise through one of two mechanisms: insertion (as for the fish) or splitting of activator peaks (Meinhardt, 1982). Under certain circumstances these mechanisms can be made to operate simultaneously [mode-tripling, see Crampin et al (2002)]. Patterns evolving on the growing domain follow a sequence which depends on the first pattern to form but is otherwise insensitive to initial conditions, and hence it has been suggested that this is a mechanism for reliable pattern formation (Crampin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%